Stable Isotope Probing of an Algal Bloom To Identify Uncultivated Members of the Rhodobacteraceae Associated with Low-Molecular-Weight Polycyclic Aromatic Hydrocarbon Degradation - Gutierrez, Tony (American Society for Microbiology, 2011)
Polycyclic aromatic hydrocarbon (PAH)-degrading bacteria associated with an algal bloom in Tampa Bay, FL, were investigated by stable isotope probing (SIP) with uniformly labeled [(13)C]naphthalene. The dominant sequences in clone libraries constructed from (13)C-enriched bacterial DNA (from naphthalene enrichments) were identified as uncharacterized members of the family Rhodobacteraceae. Quantitative PCR primers targeting the 16S rRNA gene of these uncultivated organisms were used to determine their abundance in incubations amended with unlabeled naphthalene and phenanthrene, both of which showed substantial increases in gene copy numbers during the experiments. As demonstrated by this work, the application of uniformly (13)C-labeled PAHs in SIP experiments can successfully be used to identify novel PAH-degrading bacteria in marine waters.